From Attitude to Action: Exploring Factors Influencing Switching Behavior of Public Transport Users - Ni Putu Cempaka Dharmadewi Atmaja; I Gusti Agung Ngurah Gede Eka Teja Kusuma; I Made Dauh Wijana (Journal of Consumer Sciences, 2025)
Background:  The number of vehicles in Denpasar has increased, while the public still hesitates to use public transportation, contributing to traffic congestion in Denpasar. Scientifically, this behavior can be explained by the Theory of Planned Behavior (TPB), in which perceptions of service quality and service attributes shape attitudes towards public transportation and influence switching behavior. Purpose: This study examines how these factors influence the public's willingness to switch from private vehicles to public transportation in Denpasar. Method:  The research design used is quantitative research with a non-probability sampling approach, using accidental sampling as the sampling technique. Data were obtained using a questionnaire distributed to 180 respondents who use public transportation. Using SmartPLS, the data was analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS). Findings: This study found that service quality, service-related attributes, and attitudes significantly influence the decision to switch to public transportation. Attitude partially mediates the influence of service quality and service-related attributes on the decision to switch. Conclusions: Based on the results of this study, it is recommended to improve the quality of public transportation services, particularly by reducing passenger waiting time and improving connectivity, so that bus stops are easily accessible to the public. Research implication: The results of this study are important for decision-making related to strategic planning to improve public transportation services, thereby increasing public willingness to switch to public transportation.